2020
DOI: 10.3389/fcell.2020.00359
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain Organoids: A New Tool to Investigate Parkinson’s Disease

Abstract: The study of human 3D cell culture models not only bridges the gap between traditional 2D in vitro experiments and in vivo animal models, it also addresses processes that cannot be recapitulated by either of these traditional models. Therefore, it offers an opportunity to better understand complex biology including brain development. The brain organoid technology provides a physiologically relevant context, which holds great potential for its application in modeling neurological diseases. Here, we compare diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 124 publications
0
44
0
Order By: Relevance
“…The 3DMEAs highlighted in this review present similar opportunities for in vitro analysis of brain organoids, such as the potential to record, say, dopaminergic neurons in both a substantia nigra-like region and ventral tegmental area-like region of a midbrain organoid to study Parkinson’s disease. These areas are differentially effected in Parkinson’s disease ( Smits and Schwamborn, 2020 ), representing a clear application for brain organoid modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The 3DMEAs highlighted in this review present similar opportunities for in vitro analysis of brain organoids, such as the potential to record, say, dopaminergic neurons in both a substantia nigra-like region and ventral tegmental area-like region of a midbrain organoid to study Parkinson’s disease. These areas are differentially effected in Parkinson’s disease ( Smits and Schwamborn, 2020 ), representing a clear application for brain organoid modeling.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published report showed that neuronal cell studies focused on disease use 5 cell lines per study (3 diseased, 2 control) however, the use in brain organoids was not discussed [8]. PD research utilizing organoids typically differentiate from 1 health and 1 diseased hiPSC line [11]. In depth analysis of preliminary concepts requires substantial resources and time that is not justifiable for pilot studies, especially when generating organoids [8].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most studies utilizing PD cerebral brain organoids evaluate morphology but not systemic differences in innate immunity and neurotransmission [10; 11]. Most organoid modeling of PD is based on midbrain organoids that recapitulate PD pathologies of the dopaminergic networks, neurite disfunction and abnormal localization of α-synuclein [11].…”
Section: Introductionmentioning
confidence: 99%
“…Brain organoids are self-assembled cell aggregates in which cells are not just randomly organized and interacting with each other, but exhibit a high degree of organization that closely resembles the brain tissue polarity, for which the cell-to-cell interplay is spatially and temporally regulated [ 125 , 126 ]. These bioengineered tissues can either reflect brain structures at large, in which case they are referred to as brain or cerebral organoids ( Figure 4 B), or rather resemble specific brain regions, in which case they are referred to as region-specific organoids ( Figure 4 C), such as adenohypophysis [ 127 ], cerebellar [ 128 ], forebrain [ 129 , 130 , 131 ], midbrain [ 132 ], hippocampal [ 133 ], hypothalamic [ 134 ], choroid plexus [ 135 ], optic-cup [ 136 ], or retinal organoids [ 137 ].…”
Section: Methods For Generating Brain-on-chipmentioning
confidence: 99%